Discovery of 3,6-disubstituted pyridazines as a novel class of anticancer agents targeting cyclin-dependent kinase 2: synthesis, biological evaluation and in silico insights - Ahmed Sabt; Wagdy M. Eldehna; Tarfah Al-Warhi; Ohoud J. Alotaibi; Mahmoud M. Elaasser; Howayda Suliman; Hatem A. Abdel-Aziz (Taylor & Francis Group, 2020)
Human health in the current medical era is facing numerous challenges, especially cancer. So, the therapeutic arsenal for cancer should be unremittingly enriched with novel small molecules that selectively target tumour cells with minimal toxicity towards normal cells. In this context, herein a new series of 3,6-disubstituted pyridazines 11a-r has been synthesised and evaluated for in vitro anticancer activity. They possessed good anti-proliferative action towards human breast cancer T-47D (IC50 range: 0.43 ± 0.01 − 35.9 ± 1.18 µM) and MDA-MB-231 (IC50 range: 0.99 ± 0.03 − 34.59 ± 1.13 µM) cell lines, whereas they displayed weak activity against the tested ovarian cancer cell line SKOV-3. Among the studied compounds, the methyltetrahydropyran-bearing pyridazine 11m emerged as the unique submicromolar growth inhibitor herein reported towards both T-47D (IC50 = 0.43 ± 0.01 µM) and MDA-MB-231 (IC50 = 0.99 ± 0.03 µM) cell lines. In addition, the biological results indicated that pyridazines 11l and 11m exerted an efficient alteration within the cell cycle progression as well as induction of apoptosis in both T-47D and MDA-MB-231 cells. Moreover, pyridazines 11l and 11m displayed good mean tumour S. I. values of 13.7 and 16.1 upon assessment of their cytotoxicity towards non-tumorigenic breast MCF-10A cells. Furthermore, an in silico study proposed CDK2 as a probable enzymatic target for pyridazines 11, and explored their binding interactions within the vicinity of CDK2 binding site. Subsequently, pyridazines 11e, 11h, 11l, and 11m were selected to be evaluated for their ability to inhibit CDK2, where they exerted good inhibitory activity (IC50 = 151, 43.8, 55.6 and 20.1 nM, respectively). Finally, the in silico study implied that target pyridazines 11 exhibited not only an efficient anticancer activity but also an acceptable ADME, physicochemical and druglikeness properties, specifically pyridazines 11l and 11m. Overall the obtained results from this study quite sustained our strategy and gave us a robust opportunity for further development and optimisation of 3,6-disubstituted pyridazine scaffold to enrich therapeutic arsenal with efficient and safe anticancer CDK inhibitors.